Dissertation research methods : a step-by-step guide to writing up your research in the social sciences - Adu, Philip; Adu, Philip; Miles, D. Anthony (Abingdon,Oxon: Routledge, 2024)
"Dissertation Research Methods: A Step-by-Step Guide to Writing Up Your Research in the Social Sciences focuses specifically on methodology when planning, writing and submitting your dissertation thesis. Written by two methodology experts in the social sciences, the book provides a step-by-step guide through each stage of the dissertation process. It covers all aspects of the methodological considerations needed from choosing a topic or research question, literature review, identifying research gaps, accessing potential study participants, utilizing the right sampling strategies, ways to analyze data, and writing up findings. Readers are introduced to the main research methods normally used in dissertations, and their characteristics, and are guided to choose an appropriate research method for their study, provide substantial description of the selected method, and articulate strong arguments supporting the method. The book is filled with templates, exemplars and tools to help students to write about methodology in their thesis, and to equip readers to successfully trouble shoot methodology challenges they may face. This compact book will be of use to all undergraduate and graduate students in the social sciences, Education and behavioural sciences looking for a guide to working with robust and defensible methodological principles in their dissertation research and theses"--
Includes bibliographical references and index.
Keywords: Social sciences -- Research; Social sciences -- Study and teaching; Dissertations, Academic